Answer:
The equation of the new line is [tex]y=x+9[/tex] or [tex]y-6=(x+3)[/tex]
Step-by-step explanation:
step 1
Find out the slope of the line with x-intercept (3,0) and y intercept (0,3)
The formula to calculate the slope between two points is equal to
[tex]m=\frac{y2-y1}{x2-x1}[/tex]
substitute the values
[tex]m=\frac{3-0}{0-3}=-1[/tex]
step 2
Find the slope of the new line perpendicular to the given line
we know that
If two lines are perpendicular,then their slopes are opposite reciprocal (the product of their slopes is equal to -1)
[tex]m_1*m_2=-1[/tex]
we have
[tex]m_1=-1[/tex] ----> slope of the given line
so
[tex]m_2=1[/tex] ---> slope of the new line
step 3
Find the equation of the new line in point slope form
[tex]y-y_1=m(x-x_1)[/tex]
we have
[tex]m=1[/tex]
[tex](x_1,y_1)=(-3,6)[/tex]
substitute
[tex]y-6=(1)(x+3)[/tex]
[tex]y-6=(x+3)[/tex] ----> equation in point slope form
Convert to slope intercept form
[tex]y=mx+b[/tex]
isolate the variable y
[tex]y=x+3+6[/tex]
[tex]y=x+9[/tex]